Transition to emergency distance learning amid COVID-19 pandemic through the lens of students’ subjective experience of the transformation of university learning environment - E. I. Kazakova; I. E. Kondrakova; Yu. L. Proekt (Obrazovanie i Nauka)
The aim of the current research was to identify the students’ subjective experience of the transforming learning environment according to the perceived opportunities provided by the digital learning environment of the university.Methodology and research methods. The research methodological framework is based on leading theories related to the students’ behaviour in digital learning environments (DLE). The synthesis of the theories considered made it possible to propose a theoretical model of the students’ subjective experiences in relation to DLE of the university, which was operationalised by constructing a questionnaire that reveals the students’ perception of the main components of the DLE. The following methods were employed: a questionnaire on alienation from study, a method for the assessment of students’ subjective experiences, and the Academic Motivation Scale (AMS). Previous distance learning experience was identified by the use of self-rating scales. The survey results were analysed qualitatively and quantitatively using the Cronbach Alpha coefficient, the Spearman’s rank correlation coefficient, and the Pearson’s chi-squared test. The authors also used factorial ANOVA, correspondence analysis and multiple linear regression analysis. Statistical calculations were performed using Statistica ver. 7.0 (Statsoft). 4558 students from 30 Russian universities (located in 23 subjects of Russia) took part in the research.Results. The present research demonstrated a change in the usual forms of learning activities carried out by students in the distance learning process. Distance learning is presented to students as a basis for meeting the need for subjectivity of their personality, the ability to initiate their own learning activities. Students feel that there are sufficient conditions and resources for mastering digital learning tools, and they easily adapt to the digital environment of their universities. However, in this process, the student acts as an atomised subject, weakly interacting with other people and not feeling a sense of interpersonal closeness and connectedness with others.The research findings revealed that the perceived characteristics of the DLE of the university have a direct impact on the inner states of students in the learning process. The formation of a stable social environment within the framework of the DLE, which ensures harmonious interaction and communication between the subjects of the educational process, contributes to achieving an optimal balance of students’ subjective experiences, reduces the risk of negative inner states that lead to learning demotivation, the experience of alienation from study, the growing sense of meaninglessness and emptiness in the learning process.Scientific novelty. The developed model of the influence of DLE on the subjective experiences of students in the emergence distance learning made it possible to identify significant DLE components, which determine the motivational and emotional states of students, and to establish student ratio to achieve the optimal balance of subjective experiences.Practical significance. The empirically based findings presented in this study can be used to design the DLE of the university, to determine the directions of work on the formation of psychological readiness of students for distance learning.